2015
DOI: 10.1111/tpj.12797
|View full text |Cite
|
Sign up to set email alerts
|

The RING finger E3 ligase STRF1 is involved in membrane trafficking and modulates salt‐stress response in Arabidopsis thaliana

Abstract: These authors contribute equally to this work. SUMMARYSalt stress is a detrimental factor for plant growth and development. The response to salt stress has been shown to involve components in the intracellular trafficking system, as well as components of the ubiquitin-proteasome system (UPS). In this article, we have identified in Arabidopsis thaliana a little reported ubiquitin ligase involved in salt-stress response, which we named STRF1 (Salt Tolerance RING Finger 1). STRF1 is a member of RING-H2 finger pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 64 publications
1
34
0
Order By: Relevance
“…High salt stress can cause osmotic and ionic stress [1,13]. Salt stress involved in ionic homeostasis pathway was discovered by cloning the salt overly sensitive ( SOS ) genes.…”
Section: Introductionmentioning
confidence: 99%
“…High salt stress can cause osmotic and ionic stress [1,13]. Salt stress involved in ionic homeostasis pathway was discovered by cloning the salt overly sensitive ( SOS ) genes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, In A. thaliana, BRH1 is involved in brassinosteroid-responsive19, RIE1 in seed development20, ATL2/ATL9 in defense response2122, XERICO in drought tolerance23, KEG in growth and development24, PEX2/PEX10/PEX12 in peroxisome formation2526, NLA in adaptability to nitrogen limitation27, SHA1 in shoot apical meristem maintenance28, SDIR1 in stress-responsive abscisic acid signaling29, DRIP1 / DRIP2 is in drought response30 , RHA2a/RHA2b in ABA-mediated stress signaling3132, CNI1 in the carbon/nitrogen response for growth phase transition33, SIS3 in sugar response34, XBAT32 in lateral root production by regulating the ethylene biosynthesis35, AtAIRP1 in ABA-dependent response to drought stress36, DAL1/DAL2 in regulation of programmed cell death37, DAF in anther dehiscence38, AtAIRP3 in high-salt and drought stress responses39, RSL1 in seed longevity40, AtRING1A in flowering41, COP1 in photomorphogenesis42, NERF in drought resistance43, STRF1 in salt-stress response44; in B. rapa, BrRZFP1 is involved in cold, salt and dehydration stress45; in B. napus, Bnclg1A-1D is involved in cleistogamy trait formation46.…”
mentioning
confidence: 99%
“…The RING finger ubiquitin E3 ligase SDIR1 targets SDIR1-INTERACTING PROTEIN1 to modulate the salt stress response and ABA signaling in Arabidopsis (Zhang et al, 2015). Another RING finger E3 ligase, STRF1, is a membrane trafficking-related ubiquitin ligase, which helps the plants to respond to salt stress by monitoring intracellular membrane trafficking and ROS production (Tian et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The RING finger domain appears to be a convenient scaffold that can be altered to provide functional specificity and the RING finger motif is defined as Cys-X2-Cys-X(9–39)-Cys-X(1–3)-His-X(2–3)-Cys/His-X2-Cys-X(4–48)-Cys-X2-Cys, where X is any amino acid (Borden and Freemont, 1996). Functional studies of the RING finger proteins revealed their wide range of roles in various biological processes including viral replication, signal transduction, and development (Tian et al, 2015). In contrast to two canonical RING types (C3H2C3 or C3HC4), additional types of modified RING domains including RING-V, RING-D, RING-S/T, RING-G, and RING-C2, were identified in Arabidopsis (Stone et al, 2005).…”
Section: Introductionmentioning
confidence: 99%